2019
DOI: 10.1371/journal.pone.0221131
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Pinfish in the eastern Gulf of Mexico (1998-2016)

Abstract: Forage fishes play an important role in marine ecosystems by transferring energy and nutrients through the food web. The population dynamics of forage species can therefore have cascading effects across multiple trophic levels. Here, we analyzed a 19-year dataset on Pinfish ( Lagodon rhomboides ) across four eastern Gulf of Mexico estuaries to investigate population dynamics, inter- and intra-annual synchrony, metapopulation portfolio effects, growth, and habitat effects. Young-of-year g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Orthopristis chrysoptera (pigfish) and Lagodon rhomboides (pinfish) individuals, as well as representative samples of all available primary production channels, were collected via the beam trawl protocol described above and subjected to stable isotope analysis. Orthopristis chrysoptera and L. rhomboides represent two omnivorous, ubiquitous species native to this ecosystem (Stallings et al 2015a, Faletti et al 2019, that undergo ontogenetic shifts in their diet (Stoner 1980, Darcy 1983, and use resources over similar, small home ranges (Potthoff and Allen 2003). Epiphytes, seagrass detrius and benthic microalgae are known to make up a large portion of the diet of both species (Hansen 1969, Adams 1976, Stoner and Livingston 1984, both via direct consumption and via the consumption of benthic invertebrates relying on those production channels (Carr andAdams 1973, Stoner 1980).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopristis chrysoptera (pigfish) and Lagodon rhomboides (pinfish) individuals, as well as representative samples of all available primary production channels, were collected via the beam trawl protocol described above and subjected to stable isotope analysis. Orthopristis chrysoptera and L. rhomboides represent two omnivorous, ubiquitous species native to this ecosystem (Stallings et al 2015a, Faletti et al 2019, that undergo ontogenetic shifts in their diet (Stoner 1980, Darcy 1983, and use resources over similar, small home ranges (Potthoff and Allen 2003). Epiphytes, seagrass detrius and benthic microalgae are known to make up a large portion of the diet of both species (Hansen 1969, Adams 1976, Stoner and Livingston 1984, both via direct consumption and via the consumption of benthic invertebrates relying on those production channels (Carr andAdams 1973, Stoner 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Due to different numbers of the two species captured, a total of 88 O. chrysoptera samples and 186 L. rhomboides were used to understand how each species' niche varied over the seagrass productivity regime. All fish were young-of-year (meaning they had recruited to the seagrass system in the winter through spring of the year, Chacin et al 2016, Faletti et al 2019 and were between 5 and 7 cm total length. Samples of primary production sources (algae, seagrass and epiphytes) were collected haphazardly throughout sampling and averaged over the entire study area.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the presence, abundance and species composition of seagrasses are linked to faunal richness and abundance patterns (McCloskey & Unsworth, 2015;Ray et al, 2014), but seagrass communities can vary considerably along environmental gradients of depth, nutrients, light availability, temperature and salinity (Duarte et al, 2007;Jayathilake & Costello, 2018;Uhrin & Turner, 2018). The spatial distribution and abundance of seagrass-associated fauna may also vary in response to environmental conditions (e.g., ocean temperature, phytoplankton production, pH and dissolved oxygen) that can fluctuate across space and over diel, seasonal, annual and inter-annual time-scales, especially for more mobile fauna like marine fishes (Faletti et al, 2019;Garwood et al, 2013;Unsworth et al, 2007). Additionally, seascape features like habitat connectivity and proximity to anthropogenic stressors can affect seagrass patterns and associated fauna at landscape scales (Bittner et al, 2020;Gilby et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal periodicity may be related to differing life history strategies among forage fish taxa. For example, Faletti et al (2019) and Chacin et al (2016) found that Pinfish in the eGOM were most abundant in late winter and early spring due to postspawning recruitment, while Godefroid et al (2001) found that juvenile abundance of Eucinostomus mojarras peaked in summer and early fall following early‐summer spawning. Both of these patterns are reflected in eGOM forage fish community seasonal associations shown in this study.…”
Section: Discussionmentioning
confidence: 99%